Obtenção e caracterização de um exopolissacarídeo produzido por neodeightonia phoenicum - Fonseca, Michel Da Silva (2019)
The isolation of new microorganisms and the subsequent evaluation of the potential of exopolysaccharide (EPS) production is an important tool for obtaining new macromolecules with chemical and technological properties. In this context, the present work proposed the production and characterization of an EPS obtained from an endophytic fungus isolated from Jerivá palm in Pato Branco, Paraná. The EPS produced was characterized by Fourier-transform infrared spectroscopy (FT-IR), 13C Nuclear Magnetic Resonance, Thermal Analysis (TG, DSC), X-ray diffraction (XRD), Zeta Potential, Average Particle Size, Scanning Electron Microscopy (SEM), analysis of purity and of physical parameters (solubility, emulsifying activity, water and oil holding capacity and color by CIE L* a* b* system). The fungus showed potential for EPS production and the EPS showed considerable solubility in dimethyl sulfoxide (DMSO) solutions and water, considering the solubility patterns typical of polysaccharide macromolecules. High emulsifying activity on different hydrophobic substances were also observed. The average zeta potential of the EPS was -3.81 mV, with mobility of -0.2991 mcm Vs-1, conductivity of 3.02 mS cm-1 and average particle size of 471.8 nm. Color analysis showed that the biopolymer has a whitish color with saturation of 7.52. Analysis by FT-IR showed typical polysaccharide absorption bands, the 13C NMR spectrum showed signs for 6 carbons and SEM analysis revealed a surface with a form of translucent thin films, containing granular structures in certain regions. Diffrographic analysis revealed an amorphous structure, but containing some regions with a certain crystallinity. Thermal curves showed three stages of mass loss and a high thermal stability of the sample, taking into consideration the temperature conditions commonly employed in the industrial processing of foods and pharmaceuticals.